2020
DOI: 10.3390/cancers13010083
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights into Therapy Resistance in Osteosarcoma

Abstract: Osteosarcoma, the most common bone malignancy of childhood, has been a challenge to treat and cure. Standard chemotherapy regimens work well for many patients, but there remain minimal options for patients with progressive or resistant disease, as clinical trials over recent decades have failed to significantly improve survival. A better understanding of therapy resistance is necessary to improve current treatments and design new strategies for future treatment options. In this review, we discuss known mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 145 publications
0
62
0
Order By: Relevance
“…Osteosarcoma is one of the common primary malignant tumors with an incidence rate of about three parts per million. The 5-year survival rate of patients with metastatic osteosarcoma is 15% to 30%, while that of localized osteosarcoma is 80% (149,150). Immune cells involved in the inflammation of osteosarcoma mainly include CD3 + T cells, CD14 + TAMs (tumor-associated macrophages), and CD68 + TAMs.…”
Section: The Macrophage-osteoclast Axis In Osteosarcomamentioning
confidence: 99%
“…Osteosarcoma is one of the common primary malignant tumors with an incidence rate of about three parts per million. The 5-year survival rate of patients with metastatic osteosarcoma is 15% to 30%, while that of localized osteosarcoma is 80% (149,150). Immune cells involved in the inflammation of osteosarcoma mainly include CD3 + T cells, CD14 + TAMs (tumor-associated macrophages), and CD68 + TAMs.…”
Section: The Macrophage-osteoclast Axis In Osteosarcomamentioning
confidence: 99%
“…Dox is the anthracycline most used in OS therapy. Although Dox is one of the most active drugs for the treatment of OS, some studies have shown that a subset of OS patients are resistant or may become unresponsive to this drug during chemotherapeutic treatment [ 34 , 35 ]. In addition, despite its main mechanism of action as a DNA intercalating agent and topoisomerase II inhibitor, its use is limited by severe side effects such as cardiotoxicity [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TARGET database is focused on pediatric tumors and is designed to guide the development of effective, less toxic therapies by identifying data on molecular changes in pediatric tumors. Sarcoma patients with complete follow-up data were included in our study [19] . Clinicopathological characteristics included included age, gender, race, status of surgical margin and distant metastatic status in the study .…”
Section: Gene Expression Datasets Collectionmentioning
confidence: 99%